Setinggan di Bandaraya Kuching : Kajian kes terhadap setinggan di batu tujuh dari aspek sosio-ekonomi - Zehegkiel, Piree (Universiti Malaysia Sarawak (UNIMAS), 1997)
The main objective of this study is to survey the socio-economic status of the squatters living at Sevent Mile, Kuching, Sarawak. The squatters population are 183 peoples, living in fourty dwelling houses. The researcher had interviewed 40 head of families and other household occupants to obtain data for the survey. The reseach found that there were non-existence of basic facilities such as clean water supply and eletricity even though they are living in the vicienty of a well development city or town. The people are generally poor with an average monthly income of head of family of RM441.5. The majority of the population working in private sector such as construction and manufaturing sector. This survey also researches the daily live of these people living in the squatters. The main reason for this is to explore and learn their way of life in day to day living. From the study show, it is observed that most of these people live in poverty and hardship due to lack of income and other basic facilities.